The Prevalence of Obesity and Elevated Blood Pressure in Adolescent Student Athletes From the State of Mississippi. Issue 2 (19th February 2016) - Stiefel, Eric C.; Field, Larry; Replogle, William; McIntyre, Louis; Igboechi, Oduche; Savoie, Felix H.
Background: Over the past 30 years, there has been a dramatic increase in the prevalence of childhood obesity and hypertension in the United States. The prevalence of these diagnoses among individuals participating in school-sanctioned sports has not been clearly defined. Purpose: To identify the prevalence of obesity and elevated blood pressure (BP) among student athletes and investigate associations between race, sex, type and number of sports played, and the prevalence of these diseases. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Pre–sports participation medical examinations (N = 7705) performed between 2009 and 2013 were reviewed to identify the prevalence of obesity and elevated BP and examine relationships between the type of sports played, participation in multiple sports versus a single sport, and the athlete's body weight and body mass index (BMI). Results: The prevalence of obesity was 23.5%. There was a significant association ( P < .001) between the number of sports played by the student and BMI. The risk of obesity among single-sport athletes was more than 2-fold the risk (relative risk [RR], 2.13) compared with ≥3-sport athletes and 1.42 times greater compared with 2-sport athletes (RR, 1.42). The prevalence of elevated BP was 21.2%. There was a significant association ( P < .001) between the number of sports played by the student and elevated BP. The risk of elevated BP among single-sport athletes was 1.59 times greater (RR, 1.59) than ≥3-sport athletes and 1.30 times greater compared with 2-sport athletes (RR, 1.30). Finally, obese students were 2.40 times more likely to have elevated BP compared with nonobese students ( P < .001). Conclusion: The result of this study confirms the progressive nature of the obesity epidemic and identifies the contribution of obesity to the worsening cardiometabolic profiles in student athletes. The study also identifies that participation in multiple sports and running sports decreases the individual's risk for obesity and hypertension. Clinical Relevance: The present study emphasizes the importance of screening for obesity and elevated blood pressure during the athlete's preparticipation physical examination.